Intensifikasi Profil Pelajar Pancasila dan Implikasinya Terhadap Ketahanan Pribadi Siswa - Rusnaini Rusnaini; Raharjo Raharjo; Anis Suryaningsih; Widya Noventari (Jurnal Ketahanan Nasional, 2021)
The dynamics of social, national and state life continue to develop along with the development of phenomena, science, and technology. Nowadays, national problems continue to appear in the form of various phenomena that can be said to be actual, but clichéd. In the world of education, recently, for example, several viral news have appeared in the mass media and social media about problems that can be said to be clichés, namely intolerance. News or news about the issue of intolerance, for example, is a recorded conversation between the Principal of SMKN 2 Padang and a student's parents regarding the issue of uniforms for students to wear headscarves even though they are not Muslim. It can be said that this problem is not a new problem, because a few years ago there was also a problem that was essentially the same, only in a different context, namely the prohibition of the use of the hijab in several schools in the province of Bali. Then several other problems also emerged, such as the news about the case of a teacher at SMAN 58 Ciracas, East Jakarta who intervened in the election of the OSIS chairman, as well as what happened at SMAN 6 Depok which had gone viral on social media regarding the same issue, namely the problem of selecting the OSIS chairman. All of these problems are about intolerance. However, there are not a few other problems that occur in the world of primary and secondary education such as problems of radicalism and bullying. These problems are considered as a violation of the values of Pancasila. Therefore, the Ministry of Education and Culture continues to strive to prepare and implement appropriate policies to overcome these various problems. One of the efforts made is by initiating the "Profil Pelajar Pancasila", an ideal profile of Indonesian students, of course according to Pancasila. The purpose of this study is to find out more about the "Profil Pelajar Pancasila", and what its implications are for students' personal resilience. The method used in this study is a qualitative method. The results of the study indicate that the profile referred to in the "Profil Pelajar Pancasila are noble, independent, critical reasoning, creative, mutual cooperation and global diversity. The Ministry of Education and Culture in the idea of a student profile has conveyed what are the indicators of the "Profil Pelajar Pancasila". This profile is an indicator used to measure how the criteria for Indonesian students are in accordance with Pancasila, which was initiated by the Ministry of Education and Culture's Character Strengthening Center. In his study of the "Profil Pelajar Pancasila" which contains characters that refer to Pancasila, it has implications for students' personal resilience, where the Pancasila Student Profile directs students to become individuals with character in accordance with Pancasila which is summarized in a "Profil Pelajar Pancasila".